Debiasing: a systematic discipline and delight for development profess ionals - Chambers, Robert (2018)
Do we really need debiasing, yet another word?  Yes, unless anyone can improve on it, because we need a word to describe a rigorous discipli ne we development professionals need for grounded realism. This has be en coming on me slowly. But now explorations and ‘aha!’ moments in Ind ia have accumulated and combined into an epiphany.  For […]